Respon Seleksi Indeks Dasar pada Tanaman Jagung (Zea mays L.) di Lahan Kering - I Wayan Sudika; I Nyoman Soemeinaboedhy (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
This research aimed to identificate the selection response, the avarage of yield and fresh stover weight of corn during eight cycles of mass selection with basic index technique and observe the genetic parameter of quantitative characteristics. The randomized block design was used to test the selected with 11 treatment populations. Each treatment was replicated 3 times, in order to obtain 33 experimental units. The experimental data were analyzed with analysis of variance at 5 % levels. The average treatment was tested by the LSD0.05. The selection response was obtained from the simple linear regression coefficient between the observed traits with selection cycles. The result of this research, shows the yield and fresh stover weight has a response mass selection with basic index technique per cycle at 0.230 kgplot-1 (3.39 %) and 10.633 gtan-1 (4.21 %), respectively; both of them moderate catagories. The average of yield of eighth cycle population was higher compare to initial population and Gumarang; but the same with Lamuru variety. The weight of fresh stover was the same between treatments. The yield of initial population, eighth cycle population, Gumarang and Lamuru varieties were 5.653 tha-1; 8.035 tha-1; 5.278 t ha-1 and 7.410 tha-1, respectively. The increased of plant height, total number of leaves per plant, number of fresh leaves at harvest and all yield components, were increased the yield. The increased of fresh stover weight occured when there were increased in plant height, total number of leaves, stem diameter and number of fresh leaves at harvest. The characteristic with the higher genetic effect than the environment effect found in weight of ear harvest, length of ear and yield.